A novel liquid-liquid phase separation-related gene signature for predicting prognosis in colon cancer - Wang, Shuo; Hou, Sen; Jiang, Shan; Wang, Chao; Zhang, Peipei; Ye, Yingjiang; Gao, Zhidong (Frontiers in Immunology, 2024)
BackgroundAn increasing body of evidence indicates that dysregulation of liquid-liquid phase separation (LLPS) in cellular processes is implicated in the development of diverse tumors. Nevertheless, the association between LLPS and the prognosis, as well as the tumor immune microenvironment, in individuals with colon cancer remains poorly understood.MethodsWe conducted a comprehensive evaluation of the LLPS cluster in 1010 colon cancer samples from the TCGA and GEO databases, utilizing the expression profiles of LLPS-related prognostic differentially expressed genes (DEGs). Subsequently, a LLPS-related gene signature was constructed to calculate the LLPS-related risk score (LRRS) for each individual patient.ResultsTwo LLPS subtypes were identified. Substantial variations were observed between the two LLPS subtypes in terms of prognosis, pathway activity, clinicopathological characteristics, and immune characteristics. Patients with high LRRS exhibited worse prognosis and poorer response to immunotherapy. LRRS was found to be correlated with the clinicopathological characteristics, genomic alterations, and the potential response to immune checkpoint inhibitors therapy of colon cancer patients. Additionally, the biological function of a key gene POU4F1 was verified in vitro.ConclusionsThis study highlights the crucial role of LLPS in colon cancer, LRRS can be used to predict the prognosis of colon cancer patients and aid in the identification of more effective immunotherapy strategies.